A Stable Amine‐Functionalized Microporous Metal–Organic Framework for Thermodynamically and Kinetically Selective Gas Separations. Issue 13 (4th April 2019) - Tian, Yuanyuan; Mu, Bin; Li, Bo; Li, Xing; Xu, Wei; Lin, Yichao
Abstract: An amine‐functionalized microporous metal‐organic framework (MOF)capable of thermodynamically capturing CO2 from flue gas/natural gas and kinetically separating n‐butane from iso‐butane is reported. The compound, Co2 (abim)(im)3 (abim=2‐aminobenzimidazole, im=imidazole) is both thermally and chemically robust. According to our computational modeling, it has a sharp pore size distribution with a pore diameter of ∼4.9 Å. Two functionalities are proposed for this new compound: the basic amine groups provide higher affinity to acidic CO2 molecules than N2 and CH4 based on a thermodynamic mechanism which is demonstrated by the single component measurements and binary gas mixture breakthrough experiments; the pore aperture is optimal for the kinetic separation of n‐butane and iso‐butane which have kinetic diameters of 4.3 and 5.0 Å, respectively, which is confirmed from the pressure decay measurements and the breakthrough experiment. The new MOF is promising to simultaneously confront the challenges in both CO2 capture and the separation of n‐butane from iso‐butane in industrial practice. Abstract : A stable amine‐functionalized microporous metal–organic framework was used to thermodynamically capturing CO2 from flue gas/natural gas and kinetically separating n‐butane from iso‐butane.